Structural and technical changes in Brazil:: An analysis of the declining coefficients hypothesis from 2003 to 2013 (Revista Teoria e Evidência Econômica, 2020)
The aim of this paper is to investigate the declining coefficient hypothesis to Brazil during the 2003-2013 period. It uses statistical methods applied by Obstlom (1992) and Aroche-Reyes (1995), to verify the pattern of technical change in Brazil. We built the input-output tables employing the methodology developed by Guilhoto and Sesso (2005). The results indicate a change in the structure of the economy, leading to a decrease in Leontief's direct technical coefficients. The Brazilian economy presented a positive economic preformance, from 2003 to 2013, marked by a rise in the productivity of inputs.